Volunteer Mentor Experiences of Mentoring Forced Migrants in the United Kingdom - Tynewydd, Iona; Semlyen, Joanna; North, Sophie; Rushworth, Imogen (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2021)
Research demonstrates the complex nature of supporting forced migrant populations; however, there is almost no research on volunteer experience of supporting forced migrants. This study explored the experiences of volunteer mentors in the United Kingdom. Eight participants were recruited from a single charitable organization. Data were collected using in-depth, semi-structured interviews, and verbatim transcripts were analyzed using Interpretative phenomenological analysis. Four superordinate themes emerged: “paralyzed by responsibility and powerlessness”; “weighty emotional fallout”; “navigating murky boundaries”; and “enriched with hope, joy, and inspiration.” Participants experienced a range of emotions as a result of their mentoring: from distress to inspiration. Findings suggest that focusing on achievable changes helps mentors. The mentoring relationship is hugely important to mentors but also requires careful navigation. The findings suggest that, whilst it is a fulfilling experience, support is required for volunteers mentoring forced migrants. The relative strengths and limitations of the study are considered. Theoretical implications and suggestions for organizations, clinical applications, and future research are provided.